ANALISIS KESULITAN BELAJAR MATEMATIKA PADA MATERI OPERASI HITUNG BILANGAN KELAS V - Sindi, Sindi; Asmara, Andes Safarandes; Dewi, Sinta Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This paper aims to describe the difficulties of learning mathematics for Class V Elementary Schoolstudents in Mathematics subjects. The research method used in this research is mini qualitative descriptive research is by taking a sample that has difficulties in learning mathematics, then interviewing them for their difficulties in learning mathematics material to be explained and analyzed. The research results show that in the integer material students experience difficulties in solve problems related to multiplication and division of integers. This is because the formula is difficult for studentsso you can understand, especially those related to negative multiplication and division integers. This is a note for teachers to find the right model or not monotonous, such as the use of the Discovery Learning model in study mathematics material on integer arithmetic operations.